New survey evidence on COVID-19 and Irish SMEs: Measuring the impact and policy response - Janez Kren; Martina Lawless; Conor O'Toole; Fergal McCann; John McQuinn (The Economic and Social Research Institute (ESRI), 2021)
In this paper, we use new survey data on the Irish SME population to trace out the impact of the pandemic on firms' revenues, their capacity to adjust their cost base and their usage of policy supports. Between March and October 2020 over 70 per cent of firms experienced some fall in turnover with a median fall of 25 per cent compared to 2019. The impact of the shock appears uncorrelated with past firm performance which highlights its exogenous nature. Expenditure fell by 8.5 per cent on average with 40 per cent of firms cutting spending. Losses were incurred in over 30 per cent of enterprises with a further 30 per cent just breaking even. We find that about 61 per cent of SMEs received wage subsidies, 20 per cent of firms used tax warehousing while fewer than 6 per cent of firms used lending initiatives. Policy support take-up is more likely among those more affected by the downturn, while the smallest firms appear less likely to use support than larger firms.
Keywords: 330; KMU; Coronavirus; Einnahmen; Unternehmenserfolg; Wirkungsanalyse; Irland